The Association Between Physical Self Concept, Sport and Gender in Algerian Adolescents (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
This study aims to clarify the impact of sport specialty in physical self concept and gender, and also the difference in the dimension of the physical self concept. A sample of research is made up of 169 sportsmen in different disciplines from Chlefâ€™s sport league with an average age of 18.3Â± 2.45 (soccer , volleyball, athleticism). The Physical self-description questionnaire (PSDQ) was used to measure the concept of physical self-according to multidimensional perspectives. The research results have demonstrated that the kind of sport discipline practiced by high level players has an impact on their understanding of their physical selves, and the second results might assert the general approximation which we are about to speak about. Gender issue influences self-esteem in relation to individuals, yet in the field of sport, we realize that males and females are equal at the level of all other dimensions of the questioner.